Nano-mineralogy and growth environment of Fe-Mn polymetallic crusts and nodules from the South China Sea - Ren, Yingzhi; Guan, Yao; Sun, Xiaoming; Xu, Li; Xiao, Zhenglian; Deng, Yuqi; He, Wentao (Frontiers in Marine Science, 2023)
Fe-Mn polymetallic crusts and nodules from the South China Sea (SCS) consist of submarine ferromanganese (Fe-Mn) oxide precipitates, and represent important marine mineral resource with substantial economic and scientific research value. Previous studies on the SCS polymetallic crusts and nodules were mainly focused on their bulk mineralogy and geochemistry, whilst research on their nano-mineralogy is still lacking. In this study, high-resolution transmission electron microscopy (HRTEM), Raman spectroscopic mapping, and in-situ X-ray diffraction (XRD) analysis were conducted on the nano-mineralogy of the SCS polymetallic crusts and nodules. Our findings are as follows: (1) the SCS polymetallic crusts and nodules consist mainly of layered/columnar/mottled nano-phase minerals including vernadite (δ-MnO2), birnessite, todorokite, amorphous FeOOH, H-Ti oxide (H2Ti3O7), and detritus such as quartz, feldspar, and clays; (2) An independent Ti mineral phase has been documented. Titanium forms colloidal minerals in seawater and precipitates into the crusts and nodules with other colloids, such as FeOOH and Si-Al; (3) Mineralogical analysis reveals transformation from vernadite to birnessite and todorokite. Vernadite and birnessite can be transformed to todorokite with stable structure under sub-oxic conditions. Therefore, the SCS polymetallic crusts and nodules were formed in a sub-oxic environment, and the transformation can influence the enrichment of Ni and other metals during the crust/nodule growth.